Laying hen feeding method for increasing selenium content of eggs - JING LIANGCAI (2018)
The invention belongs to the technical field of selenium-enriched eggs and particularly relates to a laying hen feeding method for increasing the selenium content of eggs. The method comprises the following specific steps that from the age of 15 days of laying hens, a feeding material is fed twice a day, and a fermented feeding liquid is fed once. The feeding material is made of the following rawmaterials including fresh edible amaranth, fresh wheat leaves, fresh dandelion leaves, corn, tomato seed meal, activated medical stone powder, mesona blumes polysaccharide and curcumin. The fermentedfeed liquid is prepared according to the following steps that fresh sonchus oleraceus is washed, pulverized, subjected to constant temperature steaming and then taken out; carrots, purple grapes and water and added, beaten, fermented and then taken out, the mixture is magnetized and filtered, and the filtrate is taken to obtain the fermented feed liquid. Environmental-protection healthy productionof the laying hens and egg